International Law in the Perspective of International Relations - Qaribilla, Roys; Umam, Ahmad Khoirul (International Journal of Social Service and Research, 2024)
Before discussing the meaning of international law, it is important to know that law is divided into two large groups, private law and public law. However, the terms these two large groups are better known as international law and international private law. The difference between the two is in the objects they regulate. International law is the law that regulates relations between countries and other legal subjects. International law can be defined as the law that regulates international scale entities. Initially, the definition of international law was only defined as law that regulates behavior and relations between countries. However, in its development, the meaning of international law has expanded to include the relationship between states and international organizations, the relationship between international organizations and other organizations, the relationship between states and individuals in special contexts, and so on. There are six subjects of international law, namely : states, international organizations, the international red cross, the vatican holy see, rebels and individuals. International Law includes a set of rules and principles established through international treaties, the practices of states, as well as legal decisions and interpretations by international institutions. Its aim is to regulate the behavior of states in maintaining peace, managing conflict, promoting cooperation, and protecting human rights. International Law covers various aspects, including the law of war (also known as international humanitarian law), refugee law, maritime law, environmental law, international trade law, international investment law, human rights law, diplomatic law.